2016
DOI: 10.1177/0031512516631070
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of the Maximal Lactate Steady State Intensity by the Rating of Perceived Exertion

Abstract: The maximal lactate steady state is the gold standard for evaluating aerobic capacity; however, it is time-consuming. The lactate minimum protocol is an easier alternative, but is not feasible and still expensive. This study investigated whether the rating of perceived exertion of 13 is an accurate predictor of lactate minimum and maximal lactate steady state intensities. Eleven physically active men performed three tests: (1) incremental exercise with workloads based on rating of perceived exertion of 10, 13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, correlation tests do not express agreement between methods, and this is a common statistical procedure error seen in the relevant literature (3,14). Therefore, the absolute agreement between T RPE and AT was tested using Lin's agreement coefficient, and significant concordance was observed (Pc = 0.84 [0.66–0.92 CI 95%]) and confirmed using the Bland-Altman technique (−4.7 [−34.2/24.7 CI 95%] watts) (Figure 3A), which produced a value similar to that reported by Madrid et al (15) for the RPE-13 protocol (−4.7 [−27.0/17.6 CI 95%] watts). Furthermore, the reliability of T RPE in AT estimation was also confirmed using the ICC (0.84 [0.64–0.94 CI 95%]), and the accuracy of the method was observable from the small CV differences of T RPE (CV = 20.74) and AT (CV = 16.44).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, correlation tests do not express agreement between methods, and this is a common statistical procedure error seen in the relevant literature (3,14). Therefore, the absolute agreement between T RPE and AT was tested using Lin's agreement coefficient, and significant concordance was observed (Pc = 0.84 [0.66–0.92 CI 95%]) and confirmed using the Bland-Altman technique (−4.7 [−34.2/24.7 CI 95%] watts) (Figure 3A), which produced a value similar to that reported by Madrid et al (15) for the RPE-13 protocol (−4.7 [−27.0/17.6 CI 95%] watts). Furthermore, the reliability of T RPE in AT estimation was also confirmed using the ICC (0.84 [0.64–0.94 CI 95%]), and the accuracy of the method was observable from the small CV differences of T RPE (CV = 20.74) and AT (CV = 16.44).…”
Section: Discussionsupporting
confidence: 81%
“…Madrid et al (15) tested the validity of an RPE score of 13 AU in MLSS estimation using the RPE-13 protocol. The study included physically active men, and the protocol for MLSS estimation consisted of 3-stage 3-minute exercises with RPE scores of 10, 13, and 16 AU at each stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have accepted the RPE as a valid submaximal test to estimate, monitor and guide the exercise intensity in various population including healthy older adults (Chung, Zhao, Liu & Quach, 2015), young athletes (Manoel et al, 2016), healthy sedentary individuals , physically active individuals (Al-Rahamneh & Eston, 2011;Madrid et al, 2016), and cardiac rehabilitation patients (Klinger, McConnell & Gardner, 2001). These studies confirmed the validity of RPE scale based on its linear relation with HR and VO 2 during exercise testing and aerobic exercises.…”
Section: Rating Of Perceived Exertion (Rpe)mentioning
confidence: 99%
“…Different studies used the MLSS for different goals, for assessment of cardiovascular or pulmonary health, evaluation of training programs, aerobic capacity, prescription of appropriate exercise intensity, and categorization of the intensity of exercise as moderate, heavy or severe 8,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%